2020
DOI: 10.3390/nu12051267
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Time-Restricted Eating on Metabolic Diseases: A Systemic Review and Meta-Analysis

Abstract: Various behavioral and physiological pathways follow a pre-determined, 24 hour cycle known as the circadian rhythm. Metabolic homeostasis is regulated by the circadian rhythm. Time-restricted eating (TRE) is a type of intermittent fasting based on the circadian rhythm. In this study, we aim to analyze systemically the effects of TRE on body weight, body composition, and other metabolic parameters. We reviewed articles from PubMed, EMBASE, and the Cochrane Library to identify clinical trials that compared TRE t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
174
3
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(185 citation statements)
references
References 56 publications
5
174
3
3
Order By: Relevance
“…Recently, several small-scale clinical studies employing TRE were performed in individuals with metabolic disorders [ 10 , 11 , 16 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. A few recent reviews evaluated the metabolic effects of TRE in both animal and human studies; however, they were not focused exclusively on the populations with MetS [ 18 , 45 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several small-scale clinical studies employing TRE were performed in individuals with metabolic disorders [ 10 , 11 , 16 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. A few recent reviews evaluated the metabolic effects of TRE in both animal and human studies; however, they were not focused exclusively on the populations with MetS [ 18 , 45 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Time-restricted feeding (TRF) is a form of IF that limits the daily food consumption to a period of 4–12 h, which induces a fasting window of 12–20 h per day [ 17 ]. However, TRF differs from IF in two aspects: (1) TRF does not require caloric restriction and (2) it requires a consistent daily eating window [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Human trials and systematic reviews on TRE have supported the findings of animal studies and have demonstrated beneficial effects on cardiovascular metabolism [ 22 ]. A recent systematic review and meta-analysis of 19 studies showed that TRE leads to weight loss and a reduction in fat mass with a preservation of fat-free mass and also has beneficials effects on cardiometabolic parameters such as blood pressure, fasting glucose concentration and cholesterol profiles [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies and trials have shown intermittent fasting diets—especially time-restricted fasting diets—through incomprehensible mechanisms, have focused on metabolic switching [ 24 ]. Time-restricted intermittent fasting methods were a promising strategy for weight loss and improvement of metabolic dysfunctions in a study that compiled several meta-analysis studies on healthy obese or overweight subjects [ 25 ]. As far as we know, there is no randomized controlled study evaluating the effects of energy restriction intermittent fasting diets on metabolic syndrome biomarkers in adult patients diagnosed to date.…”
Section: Introductionmentioning
confidence: 99%